TRENDS OF AREA, PRODUCTION AND YIELD IN WESTERN UTTAR PRADESH ‘A DISTRICT-WISE ANALYSIS OF FOODGRAINS’ - Sirohi, Rajeev (International Journal For Research In Business, Management And Accounting, 2017)
The term ‘agriculture’ literally means the science and practices of the cultivation of the soil including the raising of live stock. In economic jargon, the word includes the production and distribution of goods of agriculture origin for consumption by the population at large, domestic or foreign. In this respect it is a complex sector encompassing many products. The understanding of the contribution of agriculture to economy and of their relationship with the growth process of economy is of special significance for setting goals of agriculture development for a region and for designing a strategy for agriculture development. Agricultural development in Western Uttar Pradesh has been characterized by wide disparities. One the one hand there are districts which have experienced a very high level of per capita agricultural output caused by a sustained rise in per hectare agricultural utput. In view of this it becomes necessary to study the extent of the inequalities in agricultural productivity and to identify the factors underlying this state affairs